SUPERVISI AKADEMIK PENGAWAS UNTUK MENINGKATKAN KEMAMPUAN PEDAGOGIK GURU PADA SD NEGERI 29 PEKANBARU - Superman, Superman (Jurnal Pendidikan Guru, 2017)
Academic supervision is the professional assistance provided by the supervisor to the teacher to improve his / her competence in order to enable him to develop a more qualified learning process. The purpose of this research is to get data about 1) Academic supervision planning compiled by supervisor, 2) Implementation of supervision by academic supervisor and (3) Follow up of academic supervision result by supervisor. By using descriptive method, qualitative approach, interview data collecting technique, observation, and documentation study, supervisor research subject, principal, and teacher in SD Negeri 29 Pekanbaru, and qualitative analysis, this research show result: 1) Academic supervision planning prepared by supervisors in accordance with established procedures, 2) The implementation of academic supervision by the supervisor has been effective both seen from the techniques used, as well as procedures implementation, (3) Follow-up results supervision academic supervisors can help teachers solve problems experienced. It is suggested that the supervision of supervisors should be maintained because they can improve the pedagogic competence of teachers.